Projected paediatric cervical spine imaging rates with application of NEXUS, Canadian C-Spine and PECARN clinical decision rules in a prospective Australian cohort. Issue 5 (21st April 2021) - Phillips, Natalie; Rasmussen, Katie; McGuire, Sally; Abel, Kerrie-Ann; Acworth, Jason; Askin, Geoffrey; Brady, Robyn; Walsh, Mark; Babl, Franz E
Abstract : Background: Clinical decision rules (CDRs) are commonly used to guide imaging decisions in cervical spine injury (CSI) assessment despite limited evidence for their use in paediatric populations. We set out to determine CSI incidence, imaging rates and the frequency of previously identified CSI risk factors, and thus assess the projected impact on imaging rates if CDRs were strictly applied as a rule in our population. Methods: A single-centre prospective observational study on all aged under 16 years presenting for assessment of possible CSI to a tertiary paediatric emergency department over a year, commencing September 2015. CDR variables from the National Emergency X-Radiography Utilization Study (NEXUS) rule, Canadian C-Spine rule (CCR) and proposed Paediatric Emergency Care Applied Research Network (PECARN) rule were collected prospectively and applied post hoc. Results: 1010 children were enrolled; 973 had not received prior imaging. Of these, 40.7% received cervical spine imaging; 32.4% X-rays, 13.4% CT scan and 3% MRI. All three CDRs identified the five children (0.5%) with CSI who had not received prior imaging. If CDRs were strictly applied as a rule for imaging, projected imaging rates in our setting would be as follows: NEXUS-44% (95% CI 41% to 47.4%), CCR-at least 48.4% (95% CI 45.3% to 51.7%) and PECARN-68% (95% CI 65.1% to 71.1 % ). Conclusion: CSIs were rare (0.5% of our cohort), however, 40% of children received imaging. CDRs have been designed to guide imaging decisions; if strictly applied as a rule for imaging, the CDRs assessed in this study would increase imaging rates. Projected rates differ considerably depending on the CDR applied. These findings highlight the need for a validated paediatric-specific cervical spine imaging CDR.